2020
DOI: 10.35118/apjmbb.2020.028.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Insertion/deletion of angiotensin-converting enzyme gene polymorphism as a marker of polycystic ovary syndrome (PCOS) development in South Indian cohort women

Abstract: Polycystic ovary syndrome (PCOS) is an endocrine/metabolic disease because of the elevated levels of androgen which could lead to anovulation. The angiotensin-converting-enzyme (ACE) is a zinc metallopeptidase that converts angiotensin I to angiotensin II. ACE is bound to the plasma membrane and expressed in many tissues such as ovarian tissues. The renin-angiotensin system (RAS help the production of angiotensin, angiotensinogen, and ACE. Angiotensin II plays a major role in ovulation, steroidogenesis, follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Sharma P discussed the relationship between the VDR gene and the polymorphisms of AMH and AMHR2 genes (Apa1, Bsm1, Fok1, and Cdx2) and their influence on the levels of AMH and 25(OH)D in women with PCOS [ 17 ]. In the end, his experimental results of VDR Cdx2 polymorphism analysis showed that compared with the control group, the frequency of homozygous GG mutant genotypes in the PCOS group was significantly higher in the experimental group [ 18 ]. However, the shortcomings of these studies lie in the insufficient consideration of some performance and reference data.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma P discussed the relationship between the VDR gene and the polymorphisms of AMH and AMHR2 genes (Apa1, Bsm1, Fok1, and Cdx2) and their influence on the levels of AMH and 25(OH)D in women with PCOS [ 17 ]. In the end, his experimental results of VDR Cdx2 polymorphism analysis showed that compared with the control group, the frequency of homozygous GG mutant genotypes in the PCOS group was significantly higher in the experimental group [ 18 ]. However, the shortcomings of these studies lie in the insufficient consideration of some performance and reference data.…”
Section: Introductionmentioning
confidence: 99%